Mitral annular plane systolic excursion is an easy tool for fibrosis detection by late gadolinium enhancement cardiovascular magnetic resonance imaging in patients with hypertrophic cardiomyopathy = Excursion systolique dans le plan de l’anneau mitral : une méthode simple pour identifier les cicatrices myocardiques détectées par les séquences de rehaussements tardifs en IRM dans la cardiomyopathie hypertrophique - Dösch, Christina; Janssen, Sonja; Loßnitzer, Dirk; Rudic, Boris; Tueluemen, Erol; Heggemann, Felix; Schimpf, Rainer; Schönberg, Stefan; Borggrefe, Martin (Archives of cardiovascular diseases, 2015)
Background: Hypertrophic cardiomyopathy (HCM) causes various degrees of fibrosis resulting in left ventricular function impairment, which can be measured using mitral annular plane systolic excursion (MAPSE). Aims: To determine the values for septal, lateral and average MAPSE using cardiovascular magnetic resonance (CMR) in healthy controls and patients with HCM; and to investigate whether MAPSE correlated with the extent of fibrosis. Methods: Patients with HCM and healthy controls underwent CMR. Results: In 50 healthy controls, septal and lateral MAPSE were comparable and showed excellent intra- and inter-observer reliability. Patients with HCM had significantly reduced septal, lateral and average MAPSE compared to healthy controls. Furthermore, in patients with HCM, septal MAPSE measurements were significantly reduced compared to lateral ones. Correspondingly, the septal myocardial segments showed significantly more late gadolinium enhancement (LGE) than lateral ones. No significant differences were found between echocardiographic and CMR MAPSE measurements in healthy controls and patients with HCM. Patients who suffered a major adverse cardiac event or stroke revealed a significantly reduced MAPSE and a significantly greater LGE extent compared to event-free patients with HCM. Conclusions: MAPSE measurement using CMR is feasible, reproducible and comparable to echocardiography in healthy controls and patients with HCM. The asymmetric and mainly septal distribution of myocardial hypertrophy and fibrosis detected by LGE in patients with HCM was reflected by significantly reduced septal versus lateral MAPSE. Therefore, reduced MAPSE seems to be an easily determinable marker of fibrosis accumulation leading to left ventricular mechanical dysfunction and also seems to have a prognostic implication.
Gesehen am 05.02.2018